EFEKTIVITAS PELAKSANAAN FUNGSI LEMBAGA PEMBERDAYAAN MASYARAKAT (LPM) DALAM PEMBANGUNAN DESA DI KECAMATAN MELONGUANE KABUPATEN KEPULAUAN TALAUD - Larenggam, Pandi; Laloma, Alden; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT: UU no. 32 of 2004 and PP.No. 72 of 2005 mandated that the Institute forCommunity Empowerment (LPM) is a village community institutions that serve as aforum for community participation in the management of rural development as well asto encourage and create the access that rural communities more active role indevelopment activities. In fact the purpose of performing the functions of the LPM hasnot run optimally in most villages. On the basis of this research is to find out how theeffectiveness of the implementation of LPM function in rural development in the districtKepulauan Melonguane Talaud district.This study used a descriptive-qualitative .. Source data / research respondents were 60people who dianbil of various elements in the village. Gathering data usingquestionnaires and interviews open. Data analysis technique used was qualitativedescriptive statistical analysis.The results showed: (1) The LPM functions as a container reservoir and the voice of thepeople in rural development has not been effective. (2) The LPM functions as aninstitution of participatory village development planning has been carried out but hasnot been fully effective. (3) The LPM function in the implementation of plans /participatory rural development program is quite effective, but not optimalKeywords: effective discharge of the functions LPM, rural development.